Topical KGF treatment as a therapeutic strategy for vaginal atrophy in a model of ovariectomized mice - Ceccarelli, Simona; D'Amici, Sirio; Vescarelli, Enrica; Coluccio, Paolo; Matricardi, Pietro; Gioia, Cira; Benedetti Panici, Pierluigi; Romano, Ferdinando; Frati, Luigi; Angeloni, Antonio; Marchese, Cinzia (Journal of cellular and molecular medicine, 2014)
One of the most frequent complaints for post‐menopausal women is vaginal atrophy, because of reduction in circulating oestrogens. Treatments based on local oestrogen administration have been questioned as topic oestrogens can reach the bloodstream, thus leading to consider their safety as controversial, especially for patients with a history of breast or endometrial cancers. Recently, growth factors have been shown to interact with the oestrogen pathway, but the mechanisms still need to be fully clarified. In this study, we investigated the effect of keratinocyte growth factor (KGF), a known mitogen for epithelial cells, on human vaginal mucosa cells, and its potential crosstalk with oestrogen pathways. We also tested the in vivo efficacy of KGF local administration on vaginal atrophy in a murine model. We demonstrated that KGF is able to induce proliferation of vaginal mucosa, and we gained insight on its mechanism of action by highlighting its contribution to switch ERα signalling towards non‐genomic pathway. Moreover, we demonstrated that KGF restores vaginal trophism in vivo similarly to intravaginal oestrogenic preparations, without systemic effects. Therefore, we suggest a possible alternative therapy for vaginal atrophy devoid of the risks related to oestrogen‐based treatments, and a patent (no. RM2012A000404) has been applied for this study.